Nonequilibrium optical properties of transition metals upon ultrafast electron heating. (29th August 2018) - Bévillon, E; Stoian, R; Colombier, J P
Abstract: Femtosecond laser excitation of metals triggers swift modifications of the electronic distribution within the band structure. This has direct consequences on optical transitions transiently modifying the optical properties of materials. Influencing in real time the action of the pulse, these changes lead to substantial variations of the amount and the distribution in the energy deposited during the laser irradiation. The effect of the laser pulse can be described considering electrons heated to a range of electronic temperatures. In order to evaluate the dielectric response of ultrafast heated electrons, we performed ab initio molecular dynamic simulations coupled to the Kubo–Greenwood formalism and determined electronic temperature dependent optical properties. A series of representative transition metals was investigated: Cu, Ni, Cr, W, Ti, and Fe. The evolution of the optical properties is optically-pumped based on electronic redistribution within the density of electronic states. The proposed interpretation rely on modifications of the energy range of occupied states undergoing optical electronic transitions. It is found that the degree of filling and the shape of the d -block drive the dynamics of optical processes. Nonequilibrium optical indices, reflectivities and skin depths are reported for electron thermal excitation relevant to near-threshold laser ablation regimes. The effect of the electron temperature on optical properties allows to reconstruct and model ultrafast excitation dynamics in time-resolved diagnostics with relevance in laser micro- and nano-processing.